Factors affecting working conditions in public hospitals: A literature review. (2017) - Manyisa, Zodwa M.; van Aswegen, Elsie J.
Abstract: Working conditions in public hospitals have been of great concern to health care personnel worldwide. However, from an international perspective, there is no evidence of literature review that has been conducted on this important topic. The objective of this paper is to describe the working conditions in public hospitals. A literature review was conducted using research articles by different authors on working conditions in public hospitals. Data sources: A literature review was conducted using the following databases: Google Scholar, Pub Med, Science Direct, EHBSCO, the LANCET and MEDLINE. Articles published in English between 2000 and 2014 in peer-reviewed journals were reviewed. Search terms namely: working conditions, occupational health, public hospitals and health care personnel were used to obtain the relevant articles. Findings: Workload, HIV/AIDS epidemic, shift work, long working hours, poor infrastructure, inadequate resources and shortage of staff were found to be the main factors attributed to poor working conditions.